Anesthetic Management for Inclusion Body Myositis in Coronary Artery Bypass Graft Surgery. (24th December 2020) - Kim, Uoo
Abstract : Anesthetic management for patients with certain neuromuscular disorders may be challenging due to contraindications to triggering agents secondary to increased susceptibility for malignant hyperthermia (MH). Inclusion body myositis (IBM) is an inflammatory muscle disease that causes concern for the anesthesiologist due to potential respiratory muscle weakness and hyperkalemia with succinylcholine. Elevated serum creatinine kinase levels found in IBM also raise the possibility of increased susceptibility to MH. This case report describes a successful anesthetic course with special considerations in a patient with IBM undergoing general anesthesia for coronary artery bypass grafting (CABG) under cardiopulmonary bypass (CPB) using total intravenous anesthesia (TIVA).